2011
DOI: 10.1021/mp200027z
|View full text |Cite
|
Sign up to set email alerts
|

Injectable PAMAM Dendrimer–PEG Hydrogels for the Treatment of Genital Infections: Formulation and in Vitro and in Vivo Evaluation

Abstract: Local intravaginal drug therapy is preferred for treatment of ascending genital infections during pregnancy. In the present study, in-situ forming biodegradable hydrogel for sustained release of amoxicillin in the cervicovaginal region is described. A generation 4 poly(amidoamine) [G4-(NH2)64] dendrimer with peripheral thiopyridyl terminations is crosslinked with 8-arm polyethylene glycol (PEG) bearing thiol terminations. The hydrogels were formulated and tested in-vivo in pregnant guinea pig model for volume,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 63 publications
1
77
0
Order By: Relevance
“…Navath and co-workers reported that amoxicillin entrapped into injectable and biodegradable hydrogels obtained by cross-linking of a thiopyridyl functionalized PAMAM dendrimer [(NH2)49-G4-(NH-PDP)15] with 8-arm PEG (MW ∼ 20 kDa) is a viable therapeutic option to treat ascending genital infections during pregnancy. 76 The results confirmed that the dendritic-based hydrogels ensured a sustained intravaginal delivery of amoxicillin; additionally, the gel components were located on the epithelial surface and did not cross the fetal membrane (Fig. 5B).…”
Section: Polymer Nanoparticles and Hydrogelssupporting
confidence: 73%
“…Navath and co-workers reported that amoxicillin entrapped into injectable and biodegradable hydrogels obtained by cross-linking of a thiopyridyl functionalized PAMAM dendrimer [(NH2)49-G4-(NH-PDP)15] with 8-arm PEG (MW ∼ 20 kDa) is a viable therapeutic option to treat ascending genital infections during pregnancy. 76 The results confirmed that the dendritic-based hydrogels ensured a sustained intravaginal delivery of amoxicillin; additionally, the gel components were located on the epithelial surface and did not cross the fetal membrane (Fig. 5B).…”
Section: Polymer Nanoparticles and Hydrogelssupporting
confidence: 73%
“…Rather than exploiting the antimicrobial properties of dendrimers themselves, Navath et al investigated the use of dendrimers as a component of an in situ forming hydrogel for vaginal delivery of amoxicillin during pregnancy [137]. Topical delivery of therapeutic agents is favorable to treat ascending genital infections in pregnant women, though the delivery form must selectively treat the infection without affecting the fetus.…”
Section: Dendrimersmentioning
confidence: 99%
“…As the result of this change, an increase of sulfamethoxazole antibacterial activity and sustained release of the drug were observed. Navath et al carried out a study with amoxicillin in modified G4 PAMAM formulation, which was found to be non-toxic and enabled a sustained release of the drug in vitro [52]. The study was enhanced to in vivo assessment on pregnant guinea pigs.…”
Section: Centration (Mic) and Minimum Bactericidal Concentration (Mbcmentioning
confidence: 99%